In Brief: Chromothripsis and cancer. Issue 1 (6th August 2013) - Wyatt, Alexander W; Collins, Colin C
Abstract: Chromothripsis is a one‐step catastrophic event which plays an important role during cancer development. During chromothripsis, tens to hundreds of genomic rearrangements can occur within localized regions of the genome, and lead to the simultaneous creation of multiple cancer‐driving aberrations. Given that chromothripsis has a cancer‐wide incidence of 2–3%, its recent discovery has significant implications for our understanding of tumour biology and evolution. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.